Kinerja Dinas Sosial Dalam Penyaluran Dana Bantuan Sosial Tunai Kepada Masyarakat Didesa Marannukecamatan Lau Kabupaten Maros - HH, Isnah; Usman, Jaelan; Rasdiana, Rasdiana (Universitas Muhammadiyah Makassar, 2022)
This study aimed to explain the performance of the Social Service in equitable distribution of incidental assistance funds to the people of Marannu Village, Lau District, Maros Regency. This study used qualitative methods. Sample were 7 people that selected purposively. Research data was collected by using instruments in the form of observation, interviews and documentation. Data analysis used Miles and Huberman models. The results showed that the performance of the Social Service in equitable distribution of cash assistance to the community Marannu Village, Lau District, Maros Regency run well and it was suitable SOP if measured lbased on the performance assessment indicator. However, related data obtained from the Social Ministry was based on data was actually a result of recap years, and the lack of apparatus resources from the Social Service, and the crowd not referred to the health protocol. Keywords: Performance, Distribution of Cash Social Assistance Funds